Викорстання сучасних програмних засобів для створення фільмів з 3d елементами - Леонов, Л. О. (ХНУРЕ, 2024)
Today, technology is developing at an incredible speed, spilling over into all areas of our lives. One of these areas is cinematography, which is constantly using new technologies to create more realistic and sizzling films. Particularly appreciated is the use of 3D elements in films, which allows viewers to be more deeply immersed in the atmosphere on the screen. Thus, experiments with visual effects and advanced 3D technologies in cinema play a key role in gaining the respect of viewers and ensuring the success of films in the current entertainment market
Keywords: створення фільмів; 3d елемент